Aplikasi film edibel dan kemasan atmosfir termodifikasi untuk meningkatkan umur simpan buah salak terolah minimal - Usman Ahmad; . Yulianingsih; Meivie Lintang (Jurnal Ilmu Pertanian Indonesia, 2010)
Snake fruit is an exotic fruit from Indonesia, and nowadays has increasing in demand. There is opportunity to market minimally processed snake fruit, but this product becomes very highly perishable because of increasing in respiration rate. The objective of this research was to determine edible coating formulation in combination with modified atmosphere packaging, in order to maintain quality and to prolong shelflife of minimally processed snakefruit. The research was started by preparation of salak fruit, edible coating, measurement of respiration rate, determination of optimum atmosphere composition and critical parameter, and storage in modified atmosphere packaging. First, best atmosphere composition for minimally prcessed snakefruit was determined, then storage of minimally processed snakefruit was conducted after selection of the appropriate plastic film. Analysis was conducted on quality and organoleptic characteristics. Optimum gas composition storage for minimally processed snake fruit is 4±1%0[2] and 14±2% C0[2]. Minimally processed snake fruit with edible coatings made from pectin and chitozan combined with modified atmosphere packaging can extend shelflife and maintained quality until eight days, while without edible coating the minimally-processed snake fruit in with modified atmosphere packaging can extend until 6 days only.